Resolving Family Disputes in the Gurbet: the Role of Kurdish Peace Committee and Roj Women - Latif Tas (Oñati Socio-Legal Series)
In order to understand the different customs of the newcomers and how these work within the UK, this article discusses and evaluates the ‘informal’ Kurdish Peace Committee (KPC - a general court) and the Kurdish Women’s Committee (Roj Women – for sensitive cases involving women), as developed and practiced by members of the Kurdish diaspora (gurbet) living in the UK. Kinship, transnational marriages, frequent visits ‘back home’, and cheap telecommunications have helped Kurds to maintain strong links with Kurdish communities still living in Turkey and elsewhere in the gurbet. As a consequence of these ties, even simple disputes can affect extended family members living in the Kurdish region, the cities of Turkey, and in Europe. The Kurdish Peace Committee is involved in the settlement of such cases since, as they see it, such conflicts cannot be resolved by either British or Turkish state courts alone. Through the use of case studies, which illustrate a set of complex and interesting life stories, this article will explain how the Kurdish Peace Committee in London operates in an increasingly internal and transnational environment.